(untitled) (International Journal of Engineering Management Science, 2023)
Electricity is sent to far-off big load centers via transmission lines. These lines are vulnerable to malfunctions due to lightning strikes, short circuits, malfunctioning machinery, operator error, overloading, aging, and human error. We require the precise location of the fault occurrence in order to prevent this scenario. A group of switches at each known KM creates a fault in order to cross-check the accuracy of a set of resistors used to represent cable length in KMs. The only way to resolve this issue is to devise a system that can automatically identify a fault in an electrical transmission line and notify the relevant authorities of its precise location. Through this project you will develop a device that uses sensors to sense the incoming & outgoing values and detect anomalies. And, the system will be integrated with the IoT mechanism, to intimate the responsible people real time with the location information Moreover technical losses occur naturally and are caused because of power dissipation in transmission lines, transformers, and other power system components. Technical losses in Transmission & Distribution are computed with the information about total load and the total energy bill. While technology in the raising slopes, we should also note the increasing immoral activities. The technology stops the unauthorized use of power. With the current state of technology, the issue of unauthorized electricity use can be resolved through the Internet of Things without the need for human intervention. Large amounts of electricity will be saved with the installation of this system, making electricity available to more consumers than before in densely populated nations like China and India. The use of electricity without a valid contract with the supplier is known as power theft.